2017
DOI: 10.1177/1934578x1701200519
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Biological Activities of Laurel Tree (Laurus nobilis)

Abstract: This review summarizes the chemical composition reported up to date on Laurus nobilis L. (Lauraceae), an evergreen shrub or tree cultivated for its aromatic leaves and ornamental interest. It has been focused on non-volatile phytochemicals such as sesquiterpene lactones, flavonoids and proanthocyanidins, among others. Moreover, biological activities of laurel extracts and pure compounds have also been reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 185 publications
(341 reference statements)
5
63
0
3
Order By: Relevance
“…The qualitative examination revealed the presence of significant amounts of polyphenols and flavonoids (Table 3). Notably, this finding conforms to the report by Chandra et al [42] and Alejo-Armijo et al [43] who revealed the existence of these active constituents in both extracts. It has been shown that all these secondary metabolites have many therapeutic properties and are known to be pharmacologically active components.…”
Section: Discussionsupporting
confidence: 93%
“…The qualitative examination revealed the presence of significant amounts of polyphenols and flavonoids (Table 3). Notably, this finding conforms to the report by Chandra et al [42] and Alejo-Armijo et al [43] who revealed the existence of these active constituents in both extracts. It has been shown that all these secondary metabolites have many therapeutic properties and are known to be pharmacologically active components.…”
Section: Discussionsupporting
confidence: 93%
“…During time laurel gained a considerable importance in traditional medicine [ 13 ] and its leaf extracts or EO were used as gastroprotective and antidiarrheal [ 14 , 15 ], analgesic and anti-inflammatory [ 16 ], as antidiabetic and to decrease the risk factors of cardiovascular diseases [ 17 , 18 ]. The cytotoxic, antibacterial and antioxidant activities were also investigated, and different authors reported anticancer, antioxidant, insecticidal and molluscidal, antidiabetic, antimicrobial and antifungal activities by L. nobilis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLs are the most common allergens in bay leaf, while on the molecular level, the exocyclic α‐methylene group of SLs is the target for the allergic reaction, and is also responsible for the cross‐reactions to Compositae plants 4‐6 . Our patient was negative to SL mix; nevertheless, allergy to SL could not be ruled out as in Laurus nobilis chemovars exist which contain SLs different from the ones in the commercially available SL hapten mix 7 …”
Section: Discussionmentioning
confidence: 75%